2022
DOI: 10.3393/ac.2021.00297.0042
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Endoscopic Clipping for Acute Anastomotic Bleeding After Colorectal Surgery

Abstract: Purpose: Anastomotic bleeding after colorectal surgery is a rare, mostly self-limiting, postoperative complication that could lead to a life-threatening condition. Therefore, prompt management is required. This study aimed to evaluate the efficacy and safety of endoscopic clipping for acute anastomotic bleeding after colorectal surgery. Methods: We retrospectively reviewed the data of patients pathologically diagnosed with colorectal cancer at National Cancer Center, Korea from January 2018 to November 2020, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Postoperative bleeding is a rare but potentially fatal complication. The overall risk is around 6%, and in 1% of cases it may manifest as massive hemorrhage and hemodynamic instability [ 63 , 64 ]. During surgery, a presacral fascia injury or avulsion of the rectosacral fascia could damage the presacral and basivertebral veins, causing bleeding that is difficult to manage with conventional hemostatic maneuvers [ 65 ].…”
Section: Common Postoperative Complicationsmentioning
confidence: 99%
“…Postoperative bleeding is a rare but potentially fatal complication. The overall risk is around 6%, and in 1% of cases it may manifest as massive hemorrhage and hemodynamic instability [ 63 , 64 ]. During surgery, a presacral fascia injury or avulsion of the rectosacral fascia could damage the presacral and basivertebral veins, causing bleeding that is difficult to manage with conventional hemostatic maneuvers [ 65 ].…”
Section: Common Postoperative Complicationsmentioning
confidence: 99%
“…Intraoperative endoscopy has been used to evaluate the integrity of anastomoses, enabling the identification of bleeding at the anastomotic level or disruption of the anastomosis during surgery [36]. Endoscopy may also manage anastomotic bleeding, as it can be employed in a postoperative setting [37]. A systematic review and meta-analysis of six studies revealed that intraoperative endoscopy was linked with a decrease in postoperative AL (from 6.9% to 3.5%; OR=0.37; 95% CI, 0.21−0.68; P=0.001) and anastomotic bleeding (from 5.8% to 2.4%; OR=0.35; 95% CI, 0.15−0.82; P=0.02) in left-sided colon resection [36].…”
Section: Intraoperative Assessment Of Anastomotic Integritymentioning
confidence: 99%